Longevity of memory B cells and antibodies, as well as the polarization of effector memory helper T cells, are associated with disease severity in patients with COVID-19 in Bangladesh - Akhtar, Marjahan; Basher, Salima Raiyan; Nizam, Nuder Nower; Kamruzzaman, Mohammad; Khaton, Fatema; Banna, Hasan Al; Kaisar, M Hasanul; Karmakar, Polash Chandra; Hakim, Al; Akter, Afroza; Ahmed, Tasnuva; Tauheed, Imam; et al. (Frontiers in Immunology, 2022)
The longevity of immune responses induced by different degrees of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection provides information important to understanding protection against coronavirus disease 2019 (COVID-19). Here, we report the persistence of SARS-CoV-2 spike receptor-binding domain (RBD) specific antibodies and memory B cells recognizing this antigen in sequential samples from patients in Bangladesh with asymptomatic, mild, moderate and severe COVID-19 out to six months following infection. Since the development of long-lived memory B cells, as well as antibody production, is likely to be dependent on T helper (Th) cells, we also investigated the phenotypic changes of Th cells in COVID-19 patients over time following infection. Our results show that patients with moderate to severe COVID-19 mounted significant levels of IgG antibodies out to six months following infection, while patients with asymptomatic or mild disease had significant levels of IgG antibodies out to 3 months following infection, but these then fell more rapidly at 6 months than in patients with higher disease severity. Patients from all severity groups developed circulating memory B cells (MBCs) specific to SARS-CoV-2 spike RBD by 3 months following infection, and these persisted until the last timepoint measured at 6 months. A T helper cell response with an effector memory phenotype was observed following infection in all symptomatic patients, while patients with asymptomatic infection had no significant increases in effector Th1, Th2 and Th17 effector memory cell responses. Our results suggest that the strength and magnitude of antibody and memory B cells induced following SARS-CoV-2 infection depend on the severity of the disease. Polarization of the Th cell response, with an increase in Th effector memory cells, occurs in symptomatic patients by day 7 following infection, with increases seen in Th1, Th2, Th17 and follicular helper T cell subsets.